Analisis Pengaruh Mekanisme Katub Terhadap Daya Pada Motor Bakar 4 Tak Dengan Bahan Bakar Bensin Mesin 1500 CC - J HT Saragi; J S Purba (Jurnal MESIL (Mesin Elektro Sipil), 2021)
The increasing need for fuel and the increasingly soaring prices have resulted in many automotive manufacturers creating vehicles that consume more fuel efficiently with ideal engine performance. Torque and power are measures that describe the performance output of an internal combustion motor. These two parameters describe two different performance elements, depending on the use of the vehicle. The selection factor for the type of valve mechanism is based on its technological capability in activating engine power, increasing engine efficiency, reducing exhaust emissions, effectiveness and efficiency in reducing fuel consumption. Focusing on reducing fuel consumption, the most important thing is how there is a good system for engine control, on the engine itself, assistive devices and a good overall transmission system, so one of the valve mechanisms that promises to improve fuel efficiency is effective. Also improvements to exhaust emissions are the CVTC (Continuously Variable Timing Control) valve mechanism. The purpose of this study was to determine the effectiveness of the CVTC valve mechanism on engine power. CVTC has the ability to effectively control the intake camshaft to provide the most optimal valve timing for engine conditions, improve torque at all speed levels, and save fuel.